The mental health of Basic Health Unit nurses in times of pandemic - Alves, Letícia Jacome; Barros, Francisco Railson Bispo de; Cardoso, Andrea dos Santos (Revista de Enfermagem da UFPI, 2022)
Objective: To know the mental health of nursing professionals from a Basic Health Unit exclusively for patients with COVID-19 in the municipality of Boa Vista, Roraima. Methods: This is an exploratory and descriptive study, with a qualitative and quantitative approach, carried out with 19 nursing professionals. The data was collected between April and June 2022, using a semi-structured script of 21 mixed questions. The interviews were analyzed using Bardin’s method and the quantitative variables were submitted to the Statistical Package for the Social Sciences (SPSS) version 23.0. Results: The issue of stressors that interfere with mental health, associated with work activity during the COVID-19 pandemic, became evident. These factors had as a consequence the prevalence of psychological alterations such as fear, insecurity, anxiety, and stress. Concerning the diagnoses of mental disorders, anxiety and depression were the ones that stood out. Physical activity, psychotherapy, and religion were the coping measures adopted by the professionals interviewed. Conclusion: During the pandemic and their work practice, the professionals in this study were exposed to various stressors, developed psychological pathologies, but sought to maintain some level of mental health.